Pressure sensitive adhesive compositions comprising dispersed pressure sensitive adhesive polymers formed by emulsion polymerization of specific amounts of 2-octyl acrylate, styrene, hydroxyalkyl acrylate, monomers having at least one acid group, and optionally further monomers
The pressure-sensitive adhesive composition formed by emulsion polymerization optimizes the monomer ratio and structure, solves the problem that existing water-based pressure-sensitive adhesives are difficult to balance the adhesion and cohesion, and realizes a high-performance pressure-sensitive adhesive with a low carbon footprint.
Patent Information
- Application Number
- CN202380065587.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-06
- Publication Date
- 2025-04-18
AI Technical Summary
Existing water-based pressure-sensitive adhesives are difficult to balance between improving adhesion and cohesion, and their carbon footprint is high, making it difficult to meet environmental protection needs.
The pressure-sensitive adhesive composition formed by emulsion polymerization includes 2-octyl acrylate, styrene, hydroxyalkyl acrylate and monomers with acid groups, optimizes the monomer ratio and structure to prepare an aqueous polymer pressure-sensitive adhesive with improved adhesion/cohesion balance.
The performance of the aqueous pressure-sensitive adhesive is achieved significantly improving without reducing adhesion and cohesion, and its carbon footprint is reduced by using partial or completely biobased monomers.
Smart Images

Figure BDA0005308166630000061 
Figure BDA0005308166630000062 
Figure BDA0005308166630000111
Abstract
Description
[0001] describe
[0002] The present invention relates to a pressure-sensitive adhesive composition in the form of an aqueous polymer dispersion, which comprises a dispersed pressure-sensitive adhesive polymer formed by emulsion polymerization of 2-octyl acrylate, styrene, hydroxyalkyl acrylate and a monomer having at least one acid group and optionally other monomers. The pressure-sensitive adhesive composition can be used to produce self-adhesive articles such as self-adhesive labels, self-adhesive tapes or self-adhesive films.
[0003] Waterborne pressure sensitive adhesives are characterized by their adhesion-cohesion balance. Improved adhesion / cohesion balance can be applied to most pressure sensitive adhesive applications, and is specifically used for self-adhesive labels. For label applications, high viscosity is required to ensure high labeling line speed, and adhesives need to provide enough cohesion to obtain good convertibility simultaneously. Usually, a kind of in these performances can not be improved when not reducing another kind of performance. Another need to waterborne pressure sensitive adhesives is to reduce carbon footprint. Although this can be achieved by using part or all of bio-based monomers to produce adhesive polymers, at least part of the adhesive polymers based on bio-based monomers should also meet the adhesion / cohesion balance requirement.
[0004] WO 2009 / 129087 describes the use of 2-octyl (meth)acrylate in adhesive compositions.
[0005] WO 00 / 68335 describes contact bonding adhesives containing aqueous polymer dispersions, characterized in that the polymer is made from C1 to C12 alkyl (meth)acrylates, vinyl aromatic compounds, ethylenically unsaturated hydroxy compounds and optionally other monomers. US2020 / 0017725 A1 describes a pressure-sensitive adhesive composition comprising an emulsion polymerization product of a monomer mixture, the monomer mixture comprising alkyl (meth)acrylates, vinyl aromatic monomers, hydroxy-functional (meth)acrylate monomers and urea-substituted monomers and optionally other monomers.
[0006] It is an object of the present invention to provide water-based (ie substantially free of organic solvents) polymeric pressure-sensitive adhesives having a good or improved adhesion / cohesion balance, which are preferably based on at least partly bio-based acrylic monomers.
[0007] The present invention provides a pressure-sensitive adhesive composition in the form of an aqueous polymer dispersion, the pressure-sensitive adhesive composition comprising at least one dispersed pressure-sensitive adhesive polymer formed by emulsion polymerization of:
[0008] (i) 10% to 95% by weight, based on the sum of all monomers, of 2-octyl acrylate;
[0009] (ii) 0.1% to 5% by weight of styrene, based on the sum of all monomers;
[0010] (iii) 0.1% to 5% by weight, based on the sum of all monomers, of hydroxyalkyl acrylate;
[0011] (iv) 0.1% to 10% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group;
[0012] (v) 0% to 70% by weight, based on the sum of all monomers, of 1-octyl acrylate;
[0013] (vi) 0% to 40% by weight, based on the sum of all monomers, of isobutyl acrylate;
[0014] (vii) 0% to 70% by weight, based on the sum of all monomers, of ethyl acrylate;
[0015] (viii) 0% to 60% by weight, based on the sum of all monomers, of 2-ethylhexyl acrylate;
[0016] (ix) 0 to 20% by weight, based on the sum of all monomers, of methyl (meth)acrylate;
[0017] (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate;
[0018] (xi) optionally, at least one alkyl (meth)acrylate monomer which is different from monomers (i) to (viii) and which has a glass transition temperature of less than -20°C when polymerized as a homopolymer;
[0019] (xii) optionally, at least one functional monomer selected from the group consisting of hydroxy-functional (methyl) monomers different from those of (iii)
[0020] Acrylate monomers and urea-substituted ethylenically unsaturated monomers;
[0021] (xiii) optionally, other monomers different from (i) to (xii),
[0022] wherein the weight ratio of 2-octyl acrylate (i) to styrene (ii) and the weight ratio of 2-octyl acrylate (i) to hydroxyalkyl acrylate (iii) are each 2:1 to 100:1, preferably 20:1 to 85:1;
[0023] The glass transition temperature of the pressure-sensitive adhesive polymer is below -20°C, preferably -50°C to -25°C, determined by differential scanning calorimetry as the midpoint temperature when evaluating the second heating curve at a heating rate of 20 K / min.
[0024] It has been found that when 2-octyl acrylate is used as a bio-based comonomer in specific amounts to prepare acrylic polymer dispersions suitable for pressure sensitive adhesives for self-adhesive labels and other self-adhesive applications, very high levels of technical performance can be achieved. The performance levels are at least the same as those of completely fossil-based adhesives, and in some aspects even better.
[0025] Unless stated otherwise, the % by weight values reported for monomers in each case relate to the sum of all monomers used in the polymerization.
[0026] A pressure-sensitive adhesive is a viscoelastic adhesive that solidifies to form a film that remains permanently tacky and adhesive in the dry state at room temperature (20° C.) Adhesion to the substrate is achieved immediately by slight pressure.
[0027] The names "(meth)acrylic acid" or "(meth)acrylate" and similar names are occasionally used below as a shorthand notation for "acrylic acid or methacrylic acid" or "acrylate or methacrylate". In the name Cx-alkyl (meth)acrylate and similar names, x represents the number of carbon atoms in the alkyl group.
[0028] The terms "aqueous polymer dispersion" and "aqueous solvent" refer to a solvent system primarily based on water, preferably free of or containing less than 10 wt%, less than 5 wt%, or less than 1 wt% of organic solvents based on the total composition.
[0029] The glass transition temperature was determined by differential scanning calorimetry as the midpoint temperature when evaluating the second heating curve at a heating rate of 20 K / min (ASTM D 3418-08).
[0030] The pressure-sensitive adhesive polymer is prepared from 2-octyl acrylate. The amount of 2-octyl acrylate monomer (i) is 10% to 95% by weight based on the sum of all monomers, preferably 40% to 95% by weight, or 50% to 95% by weight, or 40% to less than 90% by weight, or 60% to less than 90% by weight. Preferably, 2-octyl acrylate is bio-based, wherein the acrylic acid component or the 2-octyl component or both are bio-based. Preferred is part of the bio-based 2-octyl acrylate, which is an ester of non-bio-based acrylic acid and bio-based 2-octanol, or completely bio-based 2-octyl acrylate, which is an ester of bio-based octenic acid and bio-based 2-octanol. Preferably, at least 50% by weight, more preferably 100% by weight of 2-octyl acrylate monomer (i) is made of bio-based 2-octanol and non-bio-based acrylic acid or bio-based acrylic acid, that is, preferably, at least the carbon atoms of the 2-octyl group of 2-octyl acrylate (i) are bio-derived.
[0031] The monomer (ii) styrene is used in an amount of 0.1 to 5% by weight, preferably 0.5 to 5% by weight, or 1 to 5% by weight, or 1 to 2% by weight, based on the sum of all monomers.
[0032] The pressure-sensitive adhesive polymer is prepared from at least one monomer (iii) which is a hydroxyalkyl (meth)acrylate. The monomer is a hydroxyalkyl (meth)acrylate having at least one hydroxyl group in the hydroxyalkyl group. The amount of the functional monomer (iii) is 0.1 wt % to 5 wt %, preferably 0.5 wt % to 5 wt % or 1 wt % to 3 wt % based on the sum of all monomers. Suitable hydroxy-functional (meth)acrylate monomers (iii) are (meth)acrylates having 1 to 10 carbon atoms in the hydroxyalkyl group. 10 -Hydroxyalkyl esters. Preferred examples are hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate. Most preferred is hydroxypropyl acrylate (including mixtures of isomers such as 2-hydroxy-propyl acrylate and 2-hydroxy-1-methylethyl acrylate).
[0033] Pressure-sensitive adhesive polymer is prepared by monomer (iv) with at least one acid group. The amount of monomer (iv) with at least one acid group is 0.1 wt % to 10 wt %, preferably 0.2 wt % to 8 wt %, more preferably 0.5 wt % to 5 wt % based on the sum of all monomers. Monomer (iv) is a monomer (acid monomer) with at least one acid group, i.e. ethylenically unsaturated acid or ethylenically unsaturated acid anhydride, and can be polymerized by free radical polymerization. Suitable acid monomers are, for example, ethylenically unsaturated carboxylic acids, ethylenically unsaturated sulfonic acids and vinylphosphonic acid. Preferred ethylenically unsaturated carboxylic acids are α, β-monoethylenically unsaturated monocarboxylic acids and dicarboxylic acids containing 3 to 6 carbon atoms in the molecule. Examples thereof are acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, vinylacetic acid and vinyllactic acid. Examples of suitable ethylenically unsaturated sulfonic acids include vinylsulfonic acid, styrenesulfonic acid, acrylamidomethylpropanesulfonic acid, sulfopropyl acrylate and sulfopropyl methacrylate. Acrylic acid, methacrylic acid, itaconic acid and mixtures thereof are preferred, with acrylic acid being particularly preferred.
[0034] The pressure-sensitive adhesive polymer is prepared from 1-octyl acrylate in an amount of 0 wt % to 70 wt %, preferably 0 wt % to 50 wt % or 0 wt % to 30 wt % or 1 wt % to 30 wt % based on the sum of all monomers. Preferably, 1-octyl acrylate is bio-based, wherein the acrylic acid component or the 1-octyl component or both are bio-based. Preferred is partially bio-based 1-octyl acrylate, which is an ester of non-bio-based acrylic acid and bio-based 1-octanol, or completely bio-based 1-octyl acrylate, which is an ester of bio-based octenic acid and bio-based 1-octanol. Preferably, at least 50 wt %, more preferably 100 wt % of 1-octyl acrylate monomers are made from bio-based 1-octanol and non-bio-based acrylic acid or bio-based acrylic acid, i.e. preferably, at least the carbon atoms of the 1-octyl group of 1-octyl acrylate are bio-derived.
[0035] The pressure-sensitive adhesive polymer is prepared from isobutyl acrylate in an amount of 0 wt % to 40 wt %, preferably 0 wt % to 20 wt % or 0 wt % to 10 wt % or 1 wt % to 10 wt %, based on the sum of all monomers. Preferably, the isobutyl acrylate is bio-based, wherein the acrylic acid component or the isobutyl component or both are bio-based. Preferred is partially bio-based isobutyl acrylate, which is an ester of non-bio-based acrylic acid and bio-based isobutyl alcohol, or completely bio-based isobutyl acrylate, which is an ester of bio-based acrylic acid and bio-based isobutyl alcohol. Preferably, at least 50 wt %, more preferably 100 wt % of the isobutyl acrylate monomer is made from bio-based isobutyl alcohol and non-bio-based acrylic acid or bio-based acrylic acid, i.e. preferably, at least the carbon atoms of the isobutyl group of the isobutyl acrylate are of bio-origin.
[0036] The pressure-sensitive adhesive polymer is prepared from ethyl acrylate in an amount of 0 wt % to 70 wt %, preferably 0 wt % to 40 wt % or 1 wt % to 40 wt % or 5 wt % to 30 wt %, based on the sum of all monomers. Preferably, the ethyl acrylate is bio-based, wherein the acrylic acid component or the ethyl component or both are bio-based. Preferred is partially bio-based ethyl acrylate, which is an ester of non-bio-based acrylic acid and bio-based ethanol, or completely bio-based ethyl acrylate, which is an ester of bio-based acrylic acid and bio-based ethanol. Preferably, at least 50 wt %, more preferably 100 wt % of the ethyl acrylate monomer is made from bio-based ethanol and non-bio-based acrylic acid or bio-based acrylic acid, i.e. preferably, at least the carbon atoms of the ethyl group of ethyl acrylate are of biological origin.
[0037] The pressure-sensitive adhesive polymer is prepared from 2-ethylhexyl acrylate in an amount of 0 to 60 wt %, preferably 1 to 40 wt % or 2 to 20 wt %, based on the sum of all monomers.
[0038] The pressure-sensitive adhesive polymer is prepared from methyl (meth)acrylate in an amount of 0 to 20 wt %, preferably 0 to 15 wt %, or 1 to 20 wt % or 2 to 15 wt %, or 2 to 10 wt %, based on the sum of all monomers.
[0039] The pressure-sensitive adhesive polymer is prepared from 0 to 10 wt %, preferably 0 to 8 wt %, or 1 to 8 wt % of vinyl acetate based on the sum of all monomers.
[0040] The pressure-sensitive adhesive polymer is optionally prepared from at least one monomer (xi) which is an alkyl (meth)acrylate monomer different from monomers (i) and (v) to (viii) and has a glass transition temperature of less than -20°C when polymerized as a homopolymer (so-called "soft" monomer). The amount of soft (meth)acrylate monomer (xi) is preferably 0% to 30% by weight, preferably 1% to 30% by weight or 2% to 25% by weight, or 3% to 20% by weight, based on the sum of all monomers. The soft monomer (xi) is preferably selected from acrylates, in particular from C3- to C6-acrylates. 10 -alkyl esters or selected from C4- to C8-alkyl acrylates. Suitable examples include n-propyl acrylate, n-butyl acrylate, n-hexyl acrylate, n-heptyl acrylate, isooctyl acrylate (2-methylheptyl acrylate) and mixtures of these monomers.
[0041] The pressure-sensitive adhesive polymer is optionally prepared from at least one functional monomer (xii) selected from hydroxyl-functional (meth)acrylate monomers and urea-substituted ethylenically unsaturated monomers different from (iii). The amount of functional monomer (xii) is preferably 0 wt % to 10 wt %, or 0.1 wt % to 10 wt % or 0.5 wt % to 7 wt % based on the sum of all monomers.
[0042] Examples of hydroxyl-functional (meth)acrylate monomers other than (iii) are N-hydroxyalkyl-(meth)acrylamides, such as N-hydroxymethyl (meth)acrylamide. The hydroxyl-functional (meth)acrylate monomers other than (iii) are present in an amount of 0 to 5% by weight or 0.5 to 5% by weight based on the sum of all monomers.
[0043] The ureido-substituted ethylenically unsaturated monomer has at least one ethylenically unsaturated free-radically polymerizable group and at least one functional group selected from ureido groups. Suitable ureido-substituted ethylenically unsaturated monomers are monomers selected from the group consisting of (meth)acrylate monomers having a substituent of the formula
[0044]
[0045] wherein X is NH or NR and R is a C1 to C4 alkyl group and the arrow at the N atom indicates the point of attachment of the substituent to the (meth)acrylate monomer. Suitable urea-substituted ethylenically unsaturated monomers are, for example, those of the formula
[0046]
[0047] wherein X is as defined above, R is hydrogen or methyl, and A is a divalent linking group, preferably a C1 to C10 alkyl group or a C2 to C4 alkyl group. Particularly preferably, ureidoalkyl (meth)acrylates having 1 to 10 C atoms, preferably 2 to 4 C atoms, in the alkyl group are used, most preferably ureidoethyl methacrylate (2-(2-oxoimidazolidin-1-yl)ethyl methacrylate; also known as ureidomethacrylate or abbreviated as UMA). The preferred amount of ureido-substituted ethylenically unsaturated monomers is 0.05% to 2% by weight, more preferably 0.1% to 2% by weight or 0.1% to 1% by weight, based on the sum of all monomers.
[0048] Pressure-sensitive adhesive polymer is optionally prepared by at least one monomer different from monomer (i) to (xii).Monomer is a copolymerizable ethylenically unsaturated compound.The amount of monomer (xii) is preferably 0 wt % to 10 wt % or 0 wt % to 5 wt % based on the sum of all monomers.Monomer is for example selected from vinyl esters of carboxylic acids containing up to 20 carbon atoms different from vinyl acetate, vinyl aromatic compounds, ethylenically unsaturated nitrile, vinyl halide, vinyl ethers containing alcohols of 1 to 10 carbon atoms, aliphatic hydrocarbons with 2 to 8 carbon atoms and one or two double bonds and (methyl) acrylamide or a mixture of these monomers.Other monomers also include phenoxyethyl glycol mono(methyl) acrylate, (methyl) glycidyl acrylate, (methyl) aminoalkyl acrylate, for example (methyl) 2-aminoethyl acrylate.Alkyl group preferably has 1 to 20 carbon atoms. Vinyl esters of carboxylic acids having 1 to 20 carbon atoms are, for example, vinyl laurate, vinyl stearate, vinyl propionate and vinyl versatate. Vinyl aromatic compounds include vinyl toluene, α-methylstyrene and p-methylstyrene, α-butylstyrene, 4-n-butylstyrene, 4-n-decylstyrene. Examples of nitriles are acrylonitrile and methacrylonitrile. Vinyl halides are ethylenically unsaturated compounds substituted with chlorine, fluorine or bromine, preferably vinyl chloride and vinylidene chloride. Examples of vinyl ethers include vinyl methyl ether or vinyl isobutyl ether. Vinyl ethers of alcohols preferably containing 1 to 4 carbon atoms are preferred. Suitable hydrocarbons having 4 to 8 carbon atoms and two ethylenic double bonds are, for example, butadiene, isoprene and chloroprene.
[0049] Preferred pressure sensitive adhesive compositions comprise at least one pressure sensitive adhesive polymer formed by emulsion polymerization of:
[0050] (i) 40% to 95% by weight, based on the sum of all monomers, of 2-octyl acrylate;
[0051] (ii) 0.5% to 5% by weight of styrene, based on the sum of all monomers;
[0052] (iii) 0.5 to 5% by weight, based on the sum of all monomers, of at least one hydroxyalkyl acrylate, preferably selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate;
[0053] (iv) 0.2 to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group, preferably selected from acrylic acid and methacrylic acid;
[0054] (v) 0% to 30% by weight, based on the sum of all monomers, of 1-octyl acrylate;
[0055] (vi) 0% to 20% by weight, based on the sum of all monomers, of isobutyl acrylate;
[0056] (vii) 0% to 40% by weight, based on the sum of all monomers, of ethyl acrylate;
[0057] (viii) 0% to 40% by weight, based on the sum of all monomers, of 2-ethylhexyl acrylate;
[0058] (ix) 0 to 10% by weight, based on the sum of all monomers, of methyl methacrylate;
[0059] (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate;
[0060] And preferably no further monomers (xi) to (xiii) are present.
[0061] Preferred pressure sensitive adhesive compositions comprise at least one pressure sensitive adhesive polymer formed by emulsion polymerization of:
[0062] (i) 50 to 80% by weight, based on the sum of all monomers, of 2-octyl acrylate;
[0063] (ii) 0.5% to 5% by weight of styrene, based on the sum of all monomers;
[0064] (iii) 0.5 to 5% by weight, based on the sum of all monomers, of a hydroxyalkyl acrylate, preferably selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate;
[0065] (iv) 0.2 to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group, preferably selected from acrylic acid and methacrylic acid;
[0066] wherein the sum of the amounts of monomers (v) to (viii) is 18 wt % to 48 wt %;
[0067] (ix) 0 to 10% by weight, based on the sum of all monomers, of methyl methacrylate;
[0068] (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate;
[0069] And preferably no further monomers (xi) to (xiii) are present.
[0070] Preferred pressure sensitive adhesive compositions comprise at least one pressure sensitive adhesive polymer formed by emulsion polymerization of:
[0071] (i) 75% to 95% by weight, based on the sum of all monomers, of 2-octyl acrylate;
[0072] (ii) 0.5% to 5% by weight of styrene, based on the sum of all monomers;
[0073] (iii) 0.5 to 5% by weight, based on the sum of all monomers, of a hydroxyalkyl acrylate, preferably selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate;
[0074] (iv) 0.2 to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group, preferably selected from acrylic acid and methacrylic acid;
[0075] wherein the sum of the amounts of monomers (v) to (viii) is from 0 wt % to 15 wt %;
[0076] (ix) 0 to 10% by weight, based on the sum of all monomers, of methyl methacrylate;
[0077] (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate;
[0078] And preferably no further monomers (xi) to (xiii) are present.
[0079] Preferably and for sustainability reasons, bio-based materials are used for the production of the pressure-sensitive adhesive polymer, which are preferably partially or completely made of partially or completely bio-based monomers. Bio-based materials are materials that are made from renewable sources and have a lower impact on the environment. They do not require all the refining steps required for petroleum-based products, which are very expensive in terms of energy. The production of CO2 is reduced, thereby reducing the impact of bio-based materials on global warming. The term "bio-based" means that the material is a biologically derived material and comes from biological materials and renewable resources. A material of renewable origin or a biomaterial is an organic material in which the carbon comes from CO2 that has been recently (on a human scale) fixed from the atmosphere by photosynthesis. Biomaterials (100% carbon of natural origin) have a carbon content greater than 10 -12 , usually about 1.2×10 -12 of 14 C / 12 C isotope ratio, while fossil materials have a ratio of 0. In practice, on time scales of at most a few decades, the isotopes 14 C is formed in the atmosphere and subsequently incorporated via photosynthesis. 14 The half-life of C is 5730 years. Therefore, materials from photosynthesis, usually plants, must have the highest content of the isotope 14 C. The content of biomaterial or biochar can be determined according to standards ASTM D 6866-12, method B (ASTM D 6866-06) and ASTM D 7026 (ASTM D 7026-04). Preferably, the pressure-sensitive adhesive polymer has a biochar content of at least 10 mol % or at least 15 mol % or more, for example 20 mol %, 30 mol % or 40 mol % or more, based on the total amount of carbon atoms in the pressure-sensitive adhesive polymer. A polymer made partially of all or partly bio-based monomers is a polymer in which not all monomers used for polymerization are partly or all bio-based monomers. Partially bio-based monomers are monomers in which not all C atoms are bio-based, for example (meth)acrylates in which only the acid part or only the alcohol part is bio-based.
[0080] Suitable bio-based materials for producing pressure-sensitive adhesive polymers are for example (meth) acrylic acid esters, wherein (meth) acrylic acid component or alcohol component or both are bio-based. The various methods of producing bio-based acrylic acid by renewable plant materials have been mentioned in EP 2626397 A1. Suitable bio-based alcohols are for example bio-based isobutyl alcohol, bio-based n-butyl alcohol, bio-based ethanol, bio-based isopentanol (3-methyl butan-1-ol), bio-based 2-octanol, bio-based 1-octanol and bio-based n-heptanol. Preferred part bio-based monomers are esters of (meth) acrylic acid and bio-based alcohol, preferably bio-based 2-octanol (i), bio-based 1-octanol (v), bio-based ethanol (vii), bio-based isobutyl alcohol (vi), bio-based n-butyl alcohol, bio-based isopentanol (3-methyl butan-1-ol), bio-based and bio-based n-heptanol. Preferred complete bio-based monomers are esters of bio-based acrylic acid and bio-based alcohol as mentioned above. Preferably, at least the carbon atoms of the alkyl group of at least one of the monomers 2-octyl acrylate, 1-octyl acrylate, isobutyl acrylate and ethyl acrylate are of bio-origin. Preferably, at least 50 wt.-%, more preferably 100 wt.-% of the 2-octyl acrylate monomer (i) is made from bio-based 2-octanol and non-bio-based acrylic acid or bio-based acrylic acid, i.e. preferably, at least the carbon atoms of the 2-octyl group of 2-octyl acrylate (i) are of bio-origin. Preferably, monomer (vi) comprises isobutyl acrylate, wherein at least the carbon atoms of the isobutyl group are of bio-origin.
[0081] The glass transition temperature (Tg) of the pressure-sensitive adhesive polymer is lower than -20°C, preferably -50°C to -25°C. Through targeted changes in monomer type and amount, those skilled in the art can prepare aqueous polymer compositions according to the present invention, the polymers of which have a glass transition temperature within the desired range. Orientation can be performed using the Fox formula. According to Fox (TG Fox, Bull. Am. Phys. Soc. 1956 [Ser. II] 1, p. 123, and according to Ullmann's Encyclopedia of Industrial Chemistry, Vol. 19, p. 18, 4th edition, Verlag Chemie, Weinheim, 1980), the glass transition temperature of the copolymer is given by the following good approximation:
[0082] 1 / T g =x 1 / T g 1 +x 2 / T g 2 +....x n / T g n ,
[0083] where x 1 , x 2 ,...x n is the mass fraction of monomers 1, 2, ... n, and T g 1 , T g 2 , ...T g n is the glass transition temperature in degrees Kelvin of a polymer composed of only one of the monomers 1, 2, ... n at a time. The T of a homopolymer of most monomers g The values are known and are listed, for example, in Ullmann's Encyclopedia of Industrial Chemistry, Volume 5, Volume A21, page 169, VCH Weinheim, 1992; other sources for the glass transition temperatures of homopolymers are, for example, J. Brandrup, EH Immergut, Polymer Handbook, 1st edition, J. Wiley, New York 1966, 2nd edition. J. Wiley, New York 1975, and 3rd edition J. Wiley, New York 1989.
[0084] The polymer dispersions used according to the invention can be obtained by free radical emulsion polymerization of ethylenically unsaturated free radical polymerizable compounds (monomers). Emulsion polymerization involves the polymerization of ethylenically unsaturated compounds (monomers) in water, using ionic and / or nonionic emulsifiers and / or protective colloids or stabilizers as surface-active compounds to stabilize the monomer droplets and the polymer particles subsequently formed from the monomers. The amount of surface-active substances used is generally 0.1 to 10 parts by weight, preferably 0.2 to 5 parts by weight, based on 100 parts by weight of the monomers to be polymerized.
[0085] A detailed description of suitable protective colloids can be found in Houben-Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], Volume XIV / 1, Makromolekulare Stoffe [Macromolecular Materials], Georg-Thieme-Verlag, Stuttgart, 1961, pages 411 to 420. Useful emulsifiers include anionic emulsifiers, cationic emulsifiers and nonionic emulsifiers. As surfactants, preference is given to using emulsifiers whose molecular weight is generally below 2000 g / mol compared to the protective colloid. When mixtures of surfactants are used, the individual components must of course be compatible with one another; in doubtful cases, this can be checked based on a few preliminary experiments. It is preferred to use anionic emulsifiers and nonionic emulsifiers as surfactants. Commonly used accompanying emulsifiers are, for example, ethoxylated fatty alcohols (EO degree: 3 to 50, alkyl groups: C8 to C 36 ) ethoxylated mono-, di- and tri-alkylphenols (EO degree: 3 to 50, alkyl group: C4 to C9), alkali metal salts of dialkyl esters of sulfosuccinic acid, and alkyl sulfates (alkyl group: C8 to C 12 ) alkali metal salts and ammonium salts, ethoxylated alkanols (EO degree: 4 to 30, alkyl group: C 12 To C 18 ), alkali metal salts and ammonium salts of ethoxylated alkylphenols (EO degree: 3 to 50, alkyl group: C4 to C9), alkali metal salts and ammonium salts of alkylsulfonic acids (alkyl group: C 12 To C 18 ) alkali metal salts and ammonium salts, and alkyl aryl sulfonic acids (alkyl group: C9 to C 18 )'s alkali metal salts and ammonium salts.
[0086] Other suitable emulsifiers are compounds of the general formula
[0087]
[0088] Wherein R5 and R6 are hydrogen or C4- to C14-alkyl and are not hydrogen at the same time, and X and Y can be alkali metal ions and / or ammonium ions. R5, R6 are preferably straight-chain or branched alkyl groups having 6 to 18 carbon atoms or hydrogen, in particular 6, 12 and 16 carbon atoms, wherein R5 and R6 are not hydrogen at the same time. X and Y are preferably sodium ions, potassium ions or ammonium ions, wherein sodium ions are particularly preferred. Compounds in which X and Y are sodium, R5 is a branched alkyl group having 12 carbon atoms and R6 is hydrogen or R5 are particularly advantageous. Industrial mixtures containing monoalkylated products in a proportion of 50% to 90% by weight are generally used. Commercially available products of suitable emulsifiers are, for example, 2A1, NP 50, OC 50, Emulgator 825, Emulgator 825S, OG, NSO, 904S, I-RA, E 3065, FES 77, AT 18, Steinapol VSL and Emulphor NPS 25. Preference is given to ionic emulsifiers or protective colloids according to the invention. Particular preference is given to ionic emulsifiers, in particular salts and acids, such as carboxylic acids, sulfonic acids and sulfates, sulfonates or carboxylates. It is also possible in particular to use mixtures of ionic and nonionic emulsifiers.
[0089] The polymerization can also be carried out in the presence of protective colloids. Protective colloids are polymeric compounds which bind large amounts of water when solvated and are able to stabilize dispersions of water-insoluble polymers. In contrast to emulsifiers, they generally do not reduce the interfacial surface tension between polymer particles and water. The number-average molecular weight of the protective colloids is, for example, above 1000 g / mol.
[0090] Emulsion polymerization can be initiated using water-soluble initiators. Water-soluble initiators are, for example, ammonium salts and alkali metal salts of peroxodisulfuric acid (e.g., sodium peroxodisulfate), hydrogen peroxide or organic peroxides, for example, tert-butyl hydroperoxide. So-called reduction-oxidation (redox) initiator systems are also suitable as initiators. Redox initiator systems are usually composed of at least one inorganic or organic reducing agent and an inorganic or organic oxidizing agent. The oxidizing component is, for example, an emulsion polymerization initiator as already mentioned above. The reducing agent component is, for example, an alkali metal salt of sulfurous acid, for example sodium sulfite, sodium bisulfite, an alkali metal salt of disulfurous acid, for example sodium bisulfite, a bisulfite addition compound of aliphatic aldehydes and ketones, for example acetone bisulfite, or a reducing agent, such as hydroxymethanesulfinic acid and its salts, or ascorbic acid. Redox initiator systems can be used together with soluble metal compounds, the metal component of which can appear in a variety of valence states. Typical redox initiator systems are, for example, ascorbic acid / iron (II) sulfate / sodium peroxodisulfate, tert-butyl hydroperoxide / sodium pyrosulfite, tert-butyl hydroperoxide / sodium hydroxymethanesulfinate. Individual components, such as the reducing agent component, may also be mixtures, such as a mixture of the sodium salt of hydroxymethanesulfinic acid and sodium pyrosulfite.
[0091] The listed initiators are usually used in the form of aqueous solutions, with the lower concentration limit being determined by the amount of water acceptable in the dispersion and the upper concentration limit being determined by the solubility of the specific compound in water. The concentration of the initiator is usually 0.1% to 30% by weight, preferably 0.5% to 20% by weight, and more preferably 1.0% to 10% by weight, based on the monomers to be polymerized. It is also possible to use two or more different initiators in the emulsion polymerization.
[0092] The polymerization can use a chain transfer agent. Preferably, no chain transfer agent is used. When a chain transfer agent is used, their amount is preferably at least 0.01 part by weight per 100 parts by weight of monomer to be polymerized, for example 0.01 to 5 parts by weight, or 0.01 to 3 parts by weight, preferably 0.01 to 0.75 parts by weight of chain transfer agent per 100 parts by weight of monomer. This makes it possible to control / reduce the molar mass of the emulsion polymer by chain termination reactions. In this procedure, the chain transfer agent is bonded to the polymer, usually to the chain end. Addition can be carried out continuously or in stages during the polymerization process. Suitable chain transfer agents are, for example, organic compounds containing sulfur in bonded form (e.g. compounds with thiol groups), aliphatic and / or araliphatic halogen compounds, aliphatic and / or aromatic aldehydes, unsaturated fatty acids (e.g. oleic acid), dienes with non-conjugated double bonds (e.g. divinylmethane, terpineol or vinylcyclohexene), hydrocarbons with easily extractable hydrogen atoms (e.g. toluene), organic acids or their salts (e.g. formic acid, sodium formate, ammonium formate), alcohols (e.g. isopropanol) and phosphorus compounds (e.g. sodium hypophosphite). Alternatively, compatible mixtures of the above chain transfer agents can be used. Chain transfer agents are generally low molecular weight compounds, having a molecular weight of less than 2000 g / mol, in particular less than 1000 g / mol. Advantageously, a small amount or the entire amount of chain transfer agent is supplied to the aqueous reaction medium before initiating the free radical polymerization. In addition, during the polymerization, a small amount or the entire amount of free radical chain transfer compounds can also be advantageously supplied to the aqueous reaction medium together with the monomers. Preferred organic compounds containing sulfur in bound form are in particular tert-butyl mercaptan, ethyl thioglycolate, mercaptoethanol, mercaptopropyltrimethoxysilane, tert-dodecyl mercaptan, thiodiglycol, ethylthioethanol, di-n-butyl sulfide, 2-isopropyl sulfide, di-n-octyl sulfide, diphenyl sulfide, diisopropyl disulfide, 2-mercaptoethanol, 1,3-mercaptopropanol, 3-mercaptopropane-1,2-diol, 1,4-mercaptobutanol, thioglycolic acid, 3-mercaptopropionic acid, mercaptosuccinic acid, thioacetic acid and thiourea. Particularly preferred thio compounds are tert-butyl mercaptan, ethyl thioglycolate, mercaptoethanol, mercaptopropyltrimethoxysilane, 2-ethylhexyl thioglycolate (EHTG), isooctyl 3-mercaptopropionic acid (IOMPA) or tert-dodecyl mercaptan (tDMK).
[0093] The emulsion polymerization is generally carried out at 30 to 130° C., preferably at 50 to 95° C. The polymerization medium may consist of water alone or of a mixture of water and a liquid miscible therewith, such as methanol. Preference is given to using water alone.
[0094] The emulsion polymerization can be carried out as a batch process or as a feed process, including staged and gradient operating modes of the feed process. Preference is given to feed processes in which a portion of the polymerization batch is charged first, heated to the polymerization temperature and the polymerization is started before the remaining polymerization batch is supplied, usually via a plurality of spatially separated feeds (one or more of which contain the monomers in pure form or in emulsified form), continuously, in stages or superimposed with a concentration gradient, while the polymerization in the polymerization zone is maintained.
[0095] It is also possible to first load the polymer seed in the polymerization to more effectively adjust the particle size. The seed latex is an aqueous dispersion of polymer microparticles with an average particle size of preferably 20nm to 40nm. The amount of the seed latex is preferably 0.01 to 0.5 parts by weight based on 100 parts by weight of monomer, particularly preferably 0.03 to 0.3 parts by weight. For example, latex based on polystyrene or based on polymethyl methacrylate is suitable. A preferred seed latex is a polystyrene seed.
[0096] The manner in which initiators are added to the polymerization vessel during the free radical aqueous emulsion polymerization is known to those of ordinary skill in the art. They can all be first added to the polymerization vessel, or used continuously or in stages at their consumption rate during the free radical aqueous emulsion polymerization. This depends specifically on the chemical nature of the initiator system and the polymerization temperature. Preferably, a portion is first loaded and the remainder is supplied to the polymerization zone at its consumption rate. In order to remove residual monomers, initiators are usually added after the actual emulsion polymerization has terminated, i.e. after at least 95% of the monomer conversion. In the feed method, the individual components can be added to the reactor from above, from the side or from below through the reactor bottom.
[0097] Emulsion polymerization generally provides an aqueous polymer dispersion with a solid content of 15% to 75% by weight, preferably 40% to 75% by weight, and particularly preferably not less than 50% by weight. In order to obtain a high reactor space / time yield, a dispersion with a very high solid content is preferred. In order to achieve a solid content of> 60% by weight, a bimodal or multimodal particle size should be established, otherwise the viscosity becomes too high and the dispersion is difficult to handle. For example, a new generation of particles can be produced by adding seeds (EP81083), by adding an excess emulsifier dose or by adding a mini-emulsion. Another advantage associated with low viscosity at high solids content is improved coating properties at high solids content. The generation of new particle generation can be carried out at any time point. It is guided by the particle size distribution seeking low viscosity. The resulting polymer is preferably used in the form of its aqueous dispersion. The size distribution of the dispersion particles can be unimodal, bimodal or multimodal.
[0098] The neutralization of the acid groups of the polymer is preferably carried out by adding a neutralizing agent during or after the polymerization, wherein the acid groups are completely or partially neutralized by adding a base. The neutralizing agent can be added, for example, in a separate feed simultaneously with the feed of the monomer mixture. After all the monomers have been fed, preferably the amount of neutralizing agent required to neutralize at least 10%, preferably 10% to 100% or 25% to 90% of the acid equivalents is present in the polymerization vessel. A particularly preferred neutralizing agent is ammonia. The pH of the polymer dispersion is preferably adjusted to a pH of greater than 4.5, more particularly to a pH between 5 and 8.
[0099] Pressure-sensitive adhesive compositions may include at least one tackifier (tackifying resin). Tackifiers are polymeric or oligomeric additives for adhesive polymers or elastomers that are generally used to improve their self-adhesiveness (tack, inherent viscosity, self-adhesiveness) so that they are firmly bonded to the surface after a short, slight contact pressure. Tackifiers include, for example, natural resins, such as rosin resins and derivatives or terpene resins formed by disproportionation or isomerization, polymerization, dimerization or hydrogenation. These can be their salt forms (with, for example, monovalent or multivalent counterions (cations)), or preferably their esterified forms. The alcohol used for esterification can be a monohydric alcohol or a polyhydric alcohol. Examples include methanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,2,3-propanetriol, pentaerythritol. Other useful tackifying resins are hydrocarbon resins, for example coumarone-indene resins, polyterpene resins, hydrocarbon resins based on unsaturated CH compounds, such as butadiene, pentene, methylbutene, isoprene, piperylene, divinylmethane, pentadiene, cyclopentene, cyclopentadiene, cyclohexadiene, styrene, α-methylstyrene, vinyltoluene. Tackifiers are known, for example, from Adhesive Age, July 1987, pp. 19-23, or Polym. Mater. Sci. Eng. 61 (1989), pp. 588-592.
[0100] Polyacrylates with low molar weight can also be used as adhesion promoters. These polyacrylates preferably have a weight-average molecular weight M of less than 50,000, in particular less than 30,000. w The tackifying polyacrylate preferably consists of at least 60% by weight, in particular at least 80% by weight, of C1-C8 alkyl (meth)acrylate. Suitable tackifiers include, for example, low molecular weight polymers and oligomers as described in WO 2013 / 117428, which have a weight-average molecular weight of less than 50 000 and a glass transition temperature of not less than -40°C to not more than 0°C, preferably not less than -35°C to not more than 0°C, which can be prepared by emulsion polymerization in the presence of at least one molecular weight regulator, and can be prepared from a monomer mixture comprising at least 40% by weight of at least one C1- to C20-alkyl (meth)acrylate.
[0101] Preferred tackifiers are selected from the group consisting of natural resins, hydrocarbon resins, tackifying polyacrylates or mixtures thereof. Particularly preferred tackifiers include natural or chemically modified rosin resins. Rosin resins are mainly composed of abietic acid or abietic acid derivatives or hydrogenated derivatives thereof. Tackifiers can be added to polymer dispersions in a simple manner. The tackifier itself is preferably in the form of an aqueous dispersion. The amount of tackifier is preferably 5 to 100 parts by weight based on 100 parts by weight of polymer (solid / solid), particularly preferably 5 to 50 parts by weight, 5 to 40 parts by weight or 10 to 40 parts by weight. Most preferably, a tackifier of biological origin is such as a natural resin, including a chemically modified natural resin.
[0102] The pressure-sensitive adhesive composition may contain other additives, such as fillers, dyes, leveling agents, flow control aids, thickeners (preferably associative thickeners, more preferably associative polyurethane thickeners), defoamers, crosslinkers, plasticizers, pigments, UV protective agents, biocides, dispersing aids or wetting agents. For better wetting of the surface, the pressure-sensitive adhesive may especially include wetting aids (wetting agents), such as fatty alcohol ethoxylates, alkylphenol ethoxylates, sulfosuccinates, nonylphenol ethoxylates, polyoxyethylene / polyoxypropylene copolymers or sodium dodecylsulfonate.
[0103] Defoamers are oil-based defoamers, water-based defoamers or silicone-based defoamers. Oil-based defoamers have an oil carrier. The oil can be mineral oil, vegetable oil, white oil or any other oil that is insoluble in the foaming medium. The oil-based defoamer also contains wax and / or hydrophobic silica to improve performance. Typical waxes are ethylene bis stearamide (EBS), paraffin, ester wax and fatty alcohol wax. These products can also have a surfactant to improve emulsification and spreading in the foaming medium. Preferred defoamers are silicone oil, hydrophobized silica particles, wax particles, natural fatty acid oil and paraffin (preferably white oil without aromatic compounds). Water-based defoamers are oils and waxes dispersed in a water base. The oil can be a mineral oil or a vegetable oil, and the wax can be a fatty alcohol, a fatty acid soap or a fatty acid ester. Silicone-based defoamers are polymers with a silicon backbone, such as polydimethylsiloxane. These can be delivered as an emulsion based on oil or water. Silicone compounds can consist of hydrophobic silica dispersed in silicone oil. Emulsifiers are added to ensure that the silicone spreads quickly and well in the foaming medium. Silicone compounds can also include siloxane diols and other modified silicone fluids. EO / PO based defoamers include polyethylene glycol and polypropylene glycol copolymers. They are delivered in oil, aqueous solution or water-based emulsion form. EO / PO copolymers generally have good dispersibility and are generally very suitable when deposition problems are a problem.
[0104] The amount of other additives is preferably 0.05 to 10 parts by weight, 0.1 to 5 parts by weight, and particularly 0.1 to 3 parts by weight per 100 parts by weight of the binder polymer (solid).
[0105] The tackified pressure-sensitive adhesive composition preferably comprises (on a solids basis)
[0106] 60 parts by weight to 95 parts by weight of a pressure-sensitive adhesive polymer,
[0107] 5 parts by weight to 40 parts by weight of a tackifier, and
[0108] 0 to 10 parts by weight of other additives.
[0109] For example
[0110] 60 parts by weight to 95 parts by weight of a pressure-sensitive adhesive polymer,
[0111] 5 parts by weight to 40 parts by weight of a tackifier, and
[0112] 0.1 to 1 part by weight per 100 parts by weight of polymer of at least one wetting agent, preferably at least one dialkyl sulfosuccinate, wherein the alkyl groups each have at least 9 carbon atoms,
[0113] 0.1 to 3 parts by weight per 100 parts by weight of polymer of at least one thickener, preferably an associative polyurethane thickener,
[0114] 0.05 to 1 part by weight per 100 parts by weight of polymer of at least one defoamer, preferably selected from silicone oils, hydrophobized silica particles, wax particles, natural fatty acid oils and paraffins (preferably aromatic-free white oils).
[0115] The non-tackified pressure-sensitive adhesive composition preferably comprises (on a solids basis)
[0116] 90 parts by weight to 99.75 parts by weight of a pressure-sensitive adhesive polymer, and
[0117] 0 to 10 parts by weight of other additives.
[0118] For example
[0119] 95 to 99.75 parts by weight of a pressure-sensitive adhesive polymer,
[0120] 0.1 to 1 part by weight per 100 parts by weight of polymer of at least one wetting agent, preferably a dialkyl sulfosuccinate,
[0121] 0.1 to 3 parts by weight per 100 parts by weight of polymer of at least one thickener, preferably an associative polyurethane thickener,
[0122] 0.05 to 1 parts by weight of at least one defoaming agent per 100 parts by weight of polymer,
[0123] Preferably it is selected from silicones, paraffins and white oils.
[0124] The pressure-sensitive adhesive composition is preferably a one-component pressure-sensitive adhesive. A one-component adhesive is an adhesive to which no external crosslinking agent (eg, isocyanate crosslinking agent) is added immediately before use.
[0125] After drying, the pressure-sensitive adhesive composition forms a film having a tack of preferably not less than 7 N / 25 mm, the tack being measured as a ring tack relative to a polished steel surface or relative to a polyethylene surface (measured as 17 g / m 2 The application rate is applied at 70g / m 2 Adhesion on paper (HERMA Etikettenpapier), measured against steel or polyethylene surfaces at 23° C. and 50% relative humidity at a tear speed of 300 mm / min (for details see Examples).
[0126] After drying, the pressure-sensitive adhesive composition forms a film having a peel strength of preferably greater than 2 N / 25 mm relative to a polyethylene surface (at 17 g / m 2 The application rate is 70g / m 2 Measured on paper (HERMA Etikettenpapier), relative to polyethylene at 23 ° C and 50% relative humidity at a tear speed of 300 mm / min, see examples for details), and relative to polished steel or glass plates greater than 7 N / m 2 .
[0127] After drying, the pressure-sensitive adhesive composition forms a film having a shear resistance of preferably at least 300 minutes at 23°C, measured as described in the Examples.
[0128] Pressure-sensitive adhesive compositions can be used to produce self-adhesive articles. Articles are at least partially coated with pressure-sensitive adhesives. Self-adhesive articles can be self-adhesive labels, self-adhesive tapes or self-adhesive films, including graphic films and protective films. Suitable carrier materials are, for example, paper, plastic films and metal foils. The self-adhesive tape of the present invention can be a tape coated with the above-mentioned substances on one or both sides. The self-adhesive label of the present invention can be a label made of paper or a thermoplastic film. Particularly preferably, the tape is made of a thermoplastic film. Suitable thermoplastic films include, for example, films made of polyolefins (e.g., polyethylene or polypropylene), polyolefin copolymers, films made of polyesters (e.g., polyethylene terephthalate), polyvinyl chloride or polyacetate. The surface of the thermoplastic polymer film is preferably corona treated. Foam carriers are also possible. The label is coated with adhesive on one side. Preferred substrates for self-adhesive articles are paper and polymer films.
[0129] The self-adhesive article is at least partially coated with a pressure-sensitive adhesive according to the invention on at least one surface. The adhesive can be applied to the article by conventional methods such as roller coating, knife coating or spreading. The application amount is preferably 0.1 g to 300 g, more preferably 2 g to 150 g solid / m 2 . After application, a drying step is usually carried out to remove the water. The water can be removed, for example, by drying at 50° C. to 150° C. The coated substrate thus obtained is used, for example, as a self-adhesive article, such as an adhesive label, adhesive tape or adhesive film. For this purpose, the carrier can be cut into tapes, labels or films before or after application of the adhesive. The side of the substrate coated with the pressure-sensitive adhesive can be covered with a release paper, for example with siliconized paper, for later use.
[0130] Substrates to which the self-adhesive articles can be advantageously applied can be, for example, metal, wood, glass, paper or plastic. The self-adhesive articles are particularly suitable for bonding to packaging surfaces, cartons, plastic packaging, books, windows, moisture barriers, motor vehicle bodies, tires or body parts.
[0131] The present invention also relates to the use of the pressure-sensitive adhesive composition for producing a self-adhesive label, a self-adhesive tape or a self-adhesive film. The present invention also relates to a self-adhesive article coated with the pressure-sensitive adhesive composition.
[0132] The invention also relates to a method for producing a self-adhesive article.
[0133] The method comprises the following steps:
[0134] (1) providing a pressure-sensitive adhesive composition as described above, and
[0135] (2) Coating at least a portion of the surface of a substrate with the pressure-sensitive adhesive composition. Example
[0136] The following input materials and abbreviations were used:
[0137] 2-EHA 2-Ethylhexyl acrylate
[0138] EA Ethyl Acrylate
[0139] bio-EA Ethyl Acrylate from Bio-based Ethanol
[0140] MMA Methyl Methacrylate
[0141] MA Methyl acrylate
[0142] S Styrene
[0143] IBA Isobutyl Acrylate
[0144] bio-IBA isobutyl acrylate with 57% biochar from bio-based isobutanol (BCH Brühl-Chemikalien Handel GmbH)
[0145] AA acrylic acid
[0146] HPA 2-Hydroxypropyl Acrylate
[0147] VAc vinyl acetate
[0148] 1-OA 1-Octyl Acrylate
[0149] bio 1-OA 1-octyl acrylate with 73% biocarbon from bio-based 1-octanol
[0150] 2-OA 2-Octyl Acrylate
[0151] bio 2-OA 2-Octyl acrylate with 73% biocarbon from bio-based 2-octanol
[0152] pphm weight parts / 100 weight parts monomer (parts / hundred parts monomer)
[0153] SC Standard conditions, 50% relative humidity, 1 bar, 23°C
[0154] Tg glass transition temperature
[0155] HDPE High Density Polyethylene
[0156] FES 77 surfactant from BASF
[0157] 2A1 Surfactant from DOW
[0158] I-SC wetting agent; anionic surfactant, dioctyl sodium sulfosuccinate
[0159] 933E Rosin ester tackifier dispersion
[0160] WO 2310 Defoamers based on white oil and paraffin
[0161] SI 2213 defoamer, modified polydimethylsiloxane
[0162] WO 2323 Defoamers based on white oil and hydrophobized silica particles
[0163] White oil colorless petroleum distillate, liquid paraffin
[0164] Preparation of pressure-sensitive adhesive polymer dispersions
[0165] Examples E1 and E2, Comparative Examples C1 to C5
[0166] The monomers listed in Table 1 were mixed with water, 1.1 pphm emulsifier FES 77 and 0.2pphm emulsifier 2A1 and 0.2pphm sodium hydroxide are mixed to prepare the emulsion feed. A reactor equipped with a stirrer, a temperature controller and several injection possibilities is charged with water, 0.05pphm ascorbic acid and heated to 85°C (C1: 90°C). 0.11pphm of sodium persulfate is added as initiator and the emulsion feed is started simultaneously with a 0.25pphm sodium persulfate feed and continued for 195 minutes (C1: 270 minutes). After a further 25 minutes of polymerization, 0.1pphm tert-butyl hydroperoxide and 0.17pphm sodium acetone bisulfite are added to the reaction mixture within 60 minutes. Finally 0.5pphm of After I-SC, the reactor was cooled to room temperature.
[0167] Examples E3 and E4, Comparative Examples C6 to C7
[0168] The monomers listed in Table 1 were mixed with water, 1.32 pphm emulsifier FES 77, 0.18pphm emulsifier 2A1 and 0.4pphm The emulsion feed was prepared by I-SC mixing. A reactor equipped with an agitator, a temperature controller and several injection possibilities was charged with water and 0.08pphm polystyrene seeds and heated to 85°C. 0.04pphm of sodium persulfate was added as an initiator, and the emulsion feed was started simultaneously with the 0.53pphm sodium persulfate feed and continued for 210 minutes. 53 minutes after the start of both feeds, 0.8pphm of polystyrene seeds was added. After the emulsion feed was completed, 0.4pphm sodium hydroxide was fed into the reactor for 45 minutes. Then, 0.15pphm tert-butyl hydroperoxide and 0.24pphm acetone sodium bisulfite were added to the reaction mixture over 60 minutes. The reactor was cooled to room temperature.
[0169] Table 1a: Monomer composition of pressure-sensitive adhesive polymer dispersions; amounts in parts by weight
[0170] E1 E2 E3 E4 C1 C2 C3 <![CDATA[C4 1) ]]> <![CDATA[C5 2) ]]> <![CDATA[C6 2) ]]> <![CDATA[C7 3) ]]> Bio-2-OA 64.5 79.5 80 53 91.5 90.5 92.5 1-OA 10 i-BA 5 EA 20 2-EHA 8 23 79.5 87.5 87.5 86.5 MMA 8 8 2 2 2 10 10 10 9 MA 8 S 2 2 1 1 1 2 1 1 2 Vc 8 8 5 5 5 8 0 HPA 2 2 2 2 2 2 1 1 2 AA 0.5 0.5 1 1 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Tg -31 -31 -41 -41 -40 -41 -41 -40 -46 -46 -46
[0171] 1) According to Example E7 of WO 00 / 68335
[0172] 2) According to Example E1 of WO 00 / 68335
[0173] 3) According to Example E2 of WO 00 / 68335
[0174] Table 1b: Monomer composition of pressure-sensitive adhesive polymer dispersions; amounts in parts by weight
[0175]
[0176]
[0177] The examples marked with C are comparative examples, and the examples marked with E are inventive examples.
[0178] Compared to the comparative examples, 2-EHA and in some examples MMA and VAc are replaced by sufficient amounts of bio 2-OA and in some examples bio 1-OA, bio-IBA and bio-EA to produce polymers according to the invention having similar glass transition temperatures.
[0179] The pressure sensitive adhesive compositions for self-adhesive labels may contain a tackifier to improve adhesion. They are prepared by mixing the pressure sensitive adhesive polymer dispersion tackifier according to Table 2.
[0180] Table 2: Pressure sensitive adhesive composition
[0181]
[0182] 1) Weight ratio of binder polymer: tackifier = 75:25 based on solids
[0183] Performance Testing
[0184] To test the adhesive properties for film labels, the pressure-sensitive adhesives of Examples E3 to E4 and C6 and C7 were coated with about 17 g / m 2 The coating amount (dry film) was coated on a 40 μm strongly oriented polypropylene (oPP) film as a support and dried at 90° C. for 3 minutes.
[0185] To test the adhesive properties for use in paper labels, the pressure-sensitive adhesives of Examples E1 and C1 (excluding tackifier) and E5 (including tackifier) and C1 to C5 were mixed at about 17 g / m 2 The adhesive polymer film was then transferred to the label paper face stock material (HERMA Etiketten papier 70 g / m 2 Unprimed).
[0186] Unless otherwise stated, the adhesive-coated substrates were stored under standard conditions for 24 hours before the adhesive properties were determined under standard conditions (SC: 23° C., 50% relative humidity).
[0187] Ring tack (fast adhesion, corresponding to FINAT test method FTM9)
[0188] Determining loop tack (also referred to as surface tack or quick adhesion) includes determining the force required to remove the adhesive applied to the carrier material from the substrate by bonding the adhesive to the substrate without pressure at a defined tearing speed at 23°C and 50% relative humidity. The test substrate is polished stainless steel, HDPE or glass. A 25mm wide and 250mm long test strip is cut from the carrier coated with the adhesive and stored at least 16 hours under SC. The two ends of the test strip are folded to about 1cm long, with the adhesive side facing inward. The adhesive strip is used to form a ring with an adhesive side facing outward, and the two ends are brought together and clamped into the upper jaw of the tensile tester. The test substrate holder is clamped into the lower jaw. The adhesive strip ring is moved downward at a speed of 300mm / min by the tensile tester, so that the adhesive side of the test strip is bonded to the substrate without additional pressure. Stop the tensile tester and move upward again immediately when the bottom edge of the upper jaw is 40mm above the substrate. The test results are reported in N / 25mm width. The maximum value (Fmax) on the display is read as a measure of surface tack. Take the average of three individual results.
[0189] Peel test (corresponding to FINAT test method FTM1)
[0190] Peel strength is the measure of the adhesion measured at 23 ° C and 50% relative humidity. In the determination of peel strength, a 25 mm wide test strip is bonded to a test sample made of HDPE, polished stainless steel or glass in each case and rolled twice with a 2 kg roller (diameter = 85 mm, Shore hardness = 80A). One end is then clamped in the upper jaw of the tensile strain tester. The adhesive strip is removed from the test surface at an angle of 180 ° at 300 mm / min, that is, the adhesive strip is bent and removed parallel to the test sample, and the force required for this is measured. The measure of peel strength is the force in N / 25 mm, obtained as the average value of five measurements. Peel strength was measured 24 hours after bonding. After this time, the adhesive strength has been fully developed. The average value of three individual results is taken.
[0191] Self-adhesive paper labels: If the peel strength is extended to a certain threshold, a rupture of the paper carrier material is observed. In this case, tensile strain is not a meaningful result but rather indicates a "paper tear".
[0192] Shear strength (corresponding to FINAT test method FTM8)
[0193] Shear strength is the measure of the cohesive force measured under SC. The carrier coated with pressure-sensitive adhesive is cut into test strips of 25 mm or 12.5 mm width. In order to measure the shear strength, the test strip is bonded to stainless steel, the bonding area is 25 × 25 mm, and rolled twice with a 2 kg roller (diameter = 85 mm, Shore hardness = 80A), stored under SC for 10 minutes or 24 hours, and then suspended stress is applied with a 2.5 kg weight. The measure of shear strength is the time (in hours) required for the weight to fall; the average value of 3 measurements is taken in each case.
[0194] The results of the performance tests are shown in the table below.
[0195] Table 3: Performance results of self-adhesive labels
[0196]
[0197] The examples show that the examples with polymers containing bio-based 2-octyl acrylate units instead of 2-ethylhexyl acrylate units (E3, E4 compared to C6 and C7) lead to improved shear strength (high cohesion) and sufficient tack and peel strength (adhesion) when used for film labels.
[0198] The examples show that copolymerization of styrene and hydroxyalkyl acrylate at 1 to 2 parts by weight each is particularly advantageous for the optimal balance of shear resistance and peel resistance, particularly advantageous for improved shear strength when used for paper labels (E1, E2 compared to C1 to C3).
[0199] The examples show that the examples with polymers comprising bio-based 2-octyl acrylate units instead of 2-ethylhexyl acrylate units (E1, E2 compared to C4 and C5) lead to improved shear strength (high cohesion) and improved peel strength (adhesion) when used for paper labels.
[0200] Recommended preparation Implementation Example (parts by weight based on solids) :
[0201]
[0202]
Claims
1. A pressure-sensitive adhesive composition in the form of an aqueous polymer dispersion, the pressure-sensitive adhesive composition comprising at least one dispersed pressure-sensitive adhesive polymer formed by emulsion polymerization of: (i) 10% to 95% by weight, preferably 40% to less than 90% by weight, based on the sum of all monomers, of 2-octyl acrylate; (ii) 0.1% to 5% by weight, preferably 0.5% to 5% by weight, of styrene, based on the sum of all monomers; (iii) 0.1% to 5% by weight, based on the sum of all monomers, of hydroxyalkyl acrylate; (iv) 0.1% to 10% by weight, preferably 0.2% to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group; (v) 0% to 70% by weight, based on the sum of all monomers, of 1-octyl acrylate; (vi) 0% to 40% by weight, based on the sum of all monomers, of isobutyl acrylate; (vii) 0% to 70% by weight, based on the sum of all monomers, of ethyl acrylate; (viii) 0 to 60% by weight, based on the sum of all monomers, of 2-ethylhexyl acrylate; (ix) 0 to 20% by weight, preferably 2 to 15% by weight, based on the sum of all monomers, of methyl (meth)acrylate; (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate; (xi) optionally, at least one alkyl (meth)acrylate monomer which is different from monomers (i) and (v) to (viii) and which has a glass transition temperature of less than -20°C when polymerized as a homopolymer; (xii) optionally, at least one functional monomer selected from hydroxy-functional (meth)acrylate monomers and urea-substituted ethylenically unsaturated monomers different from (iii); (xiii) optionally, other monomers different from (i) to (xii), wherein the weight ratio of 2-octyl acrylate (i) to styrene (ii) and the weight ratio of 2-octyl acrylate (i) to hydroxyalkyl acrylate (iii) are each 2:1 to 100:1, preferably 20:1 to 85:1; The glass transition temperature of the pressure-sensitive adhesive polymer is below -20°C, preferably -50°C to -25°C, determined by differential scanning calorimetry as the midpoint temperature when evaluating the second heating curve at a heating rate of 20 K / min.
2. The pressure-sensitive adhesive composition according to claim 1, wherein the pressure-sensitive adhesive composition comprises at least one tackifier in an amount of 5 to 40 parts by weight based on 100 parts by weight of the polymer, and the tackifier is selected from natural resins, hydrocarbon resins, tackified polyacrylates or mixtures thereof. 3 . The pressure-sensitive adhesive composition according to claim 1 , wherein the hydroxyalkyl acrylate is hydroxypropyl acrylate.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein 0.2 to 8 wt% of monomer (iv) is used, and the monomer is selected from acrylic acid, methacrylic acid and itaconic acid.
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein at least the carbon atom of the alkyl group of at least one of the monomers 2-octyl acrylate, 1-octyl acrylate, isobutyl acrylate and ethyl acrylate is of bio-origin. 6 . The pressure-sensitive adhesive composition according to claim 1 , wherein the 2-octyl acrylate monomer (i) is made of bio-based 2-octanol and non-bio-based acrylic acid or bio-based acrylic acid. 7 . The pressure-sensitive adhesive composition according to claim 1 , wherein monomer (vi) comprises 2-hydroxypropyl acrylate in an amount of 0.5 to 5 wt % based on the total of all monomers.
8. The pressure-sensitive adhesive composition according to any one of claims 1 to 7, wherein monomer (xii) comprises 2-(2-oxoimidazolidin-1-yl)ethyl methacrylate in an amount of 0.05 wt% to 2 wt% based on the total of all monomers.
9. The pressure-sensitive adhesive composition according to any one of claims 1 to 8, comprising at least one pressure-sensitive adhesive polymer formed by emulsion polymerization of: (i) 40% to 95% by weight, based on the sum of all monomers, of 2-octyl acrylate; (ii) 0.5% to 5% by weight of styrene, based on the sum of all monomers; (iii) 0.5 to 5% by weight, based on the sum of all monomers, of at least one hydroxyalkyl acrylate, preferably selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate; (iv) 0.2% to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group, preferably selected from acrylic acid and methacrylic acid; (v) 0% to 30% by weight, based on the sum of all monomers, of 1-octyl acrylate; (vi) 0% to 20% by weight, based on the sum of all monomers, of isobutyl acrylate; (vii) 0% to 40% by weight, based on the sum of all monomers, of ethyl acrylate; (viii) 0 to 40% by weight, based on the sum of all monomers, of 2-ethylhexyl acrylate; (ix) 0 to 15% by weight, based on the sum of all monomers, of methyl (meth)acrylate; (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate; And preferably no further monomers (xi) to (xiii) are present.
10. The pressure-sensitive adhesive composition of claim 9, comprising at least one pressure-sensitive adhesive polymer formed by emulsion polymerization of: (i) 50 to 80% by weight, based on the sum of all monomers, of 2-octyl acrylate; (ii) 0.5% to 5% by weight of styrene, based on the sum of all monomers; (iii) 0.5 to 5% by weight, based on the sum of all monomers, of a hydroxyalkyl acrylate, preferably selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate; (iv) 0.2% to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group, preferably selected from acrylic acid and methacrylic acid; wherein the sum of the amounts of monomers (v) to (viii) is 18 wt % to 48 wt %; (ix) 0 to 15% by weight, based on the sum of all monomers, of methyl (meth)acrylate; (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate; And preferably no further monomers (xi) to (xiii) are present.
11. The pressure-sensitive adhesive composition of claim 9, comprising at least one pressure-sensitive adhesive polymer formed by emulsion polymerization of: (i) 75% to 95% by weight, based on the sum of all monomers, of 2-octyl acrylate; (ii) 0.5% to 5% by weight of styrene, based on the sum of all monomers; (iii) 0.5 to 5% by weight, based on the sum of all monomers, of a hydroxyalkyl acrylate, preferably selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate and hydroxybutyl acrylate; (iv) 0.2% to 8% by weight, based on the sum of all monomers, of at least one monomer having at least one acid group, preferably selected from acrylic acid and methacrylic acid; wherein the sum of the amounts of monomers (v) to (viii) is from 0 wt % to 15 wt %; (ix) 0 to 15% by weight, based on the sum of all monomers, of methyl (meth)acrylate; (x) 0 to 10% by weight, based on the sum of all monomers, of vinyl acetate; And preferably no further monomers (xi) to (xiii) are present. 12 . The pressure-sensitive adhesive composition according to claim 1 , wherein the pressure-sensitive adhesive composition is a one-component pressure-sensitive adhesive to which no external crosslinking agent is added immediately before use.
13. Use of the pressure-sensitive adhesive composition according to any of the preceding claims for producing self-adhesive labels, self-adhesive tapes or self-adhesive films.
14. A self-adhesive article coated with the pressure-sensitive adhesive composition according to any one of claims 1 to 12.
15. A method for producing a self-adhesive article, the method comprising the steps of: (1) providing a pressure-sensitive adhesive composition according to any one of claims 1 to 12; as well as (2) Coating at least a portion of a substrate surface with the pressure-sensitive adhesive composition.
Citation Information
Patent Citations
Adhesive strips on the basis of bio-based monomers
EP2626397A1
Pressure Sensitive Adhesive Compositions and Methods for Preparing Same
US20200017725A1
Contact bonding adhesives
WO2000068335A1
2-octyl (METH)acrylate adhesive composition
WO2009129087A1
Aqueous polymer dispersion that can be used as a tackifier for adhesives and can be produced by emulsion polymerisation based on c1 to c20 alkyl (METH)acrylates
WO2013117428A1